MORAL RESPONSIBILITY AND THE PRINCIPLES OF ACTION IN ST. AUGUSTINE - Jeske Vahl, Matheus (2021)
The problem of moral responsibility is an issue to be addressed in view of the quality of human actions, which requires an explanation of the origin and meaning of evil that eventually results from them. In the late ancient thought, this is done on the horizon of philosophy of the mind. In Augustine, this theme is treated from the understanding of a psychical faculty that guarantees man the maximum of freedom, namely, the will, the effect of which is understood in reference to a pole of maximum of transcendence – God, from whom the principles in which the human reason must be articulated to guide his freedom, in coherence with the Truth. Therefore, it is in the internal structure of the human mind that Augustine anchors the origin and ultimate foundation of all moral action, for which each individual is solely responsible in the face of reality and in face of the God.